Thermo-visco-elastic Rayleigh waves under the influence of couple-stress and gravity - Tapan Kumar Das; P. R. Sengupta; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with thermo-visco-elastic Rayleigh waves under the influence of couple-stresses and gravity. A more general phase velocity equation for these waves is derived. It is shown that the phase velocity equation reduces to that of the classical elastic Rayleigh waves in the absence of the couple-stress parameter, viscosity and gravity.